THE RADICALIZATION OF ISLAM THROUGH SEMI-STATE INSTITUTIONS: A Case Study of the Role of MUI after the New Order - Ahmad Zainul Hamdi (Asia-Pacific Journal on Religion and Society, 2022)
At the beginning of its formation, MUI showed itself as a religious institution whose fatwas were often supportive of government policies. After the political reformation in 1998, MUI tried to voice its demands and try to get a new role. In this situation, the most ready force was conservative Muslims who started to enter MUI in the late 1990s and then added by the entry of some radical Islamic groups just before the fall of Soeharto in 1998. The inevitable consequence was the changing nature of MUI from an apolitical organization to a political tool played by these Muslim groups. Controlling MUI is one of the strategies of radical-conservative Islamic groups to achieve their political agendas. They use two strategies: non-structural and structural. Non-structural strategies are carried out through demonstrations, intimidation, and attacking people or groups seen as enemies of Islam. Meanwhile, structural strategies are carried out by forming or cooperating with Islamist political parties, alliances with state forces that are considered powerful such as the military, and controlling or controlling semi-state Islamic institutions such as the MUI. Controlling the MUI has given radical Muslim groups two advantages: first, to Islamize Indonesia from within and second, Islamic legitimacy for its various non-structural activities. When radical-conservative Muslims succeed in controlling the MUI, their Islamic views can be easily propagated because their voice has become the voice of the MUI which, in some cases, is claimed to be the official voice of the Indonesian government and Muslims.